Microclima em diferentes fitofisionomias de floresta de altitude na Mata Atlântica - Salim Neto, Salim Calil (2017)
The Atlantic Forest Biome is recognized for its high biodiversity and for harboring species endemic to its associated ecosystems. Over altitudinal gradient is observed the formation of altitude ecosystems that differ markedly in their phytophysiognomic structures. The present study aimed to study the influence of the phytophysiognomy on the definitionof the microclimate near the ground. The study area is located in the Forno Grande State Park, Castelo, ES, Brazil (lat. 20°31’13”S; long. 41°06’21”W) and consists of a slope facing east with 1.1 ha, at 1,450m altitude. Over a year, threemicroclimatic studies were carried out. In the first one the aim was to characterize the net radiation (Rn), photosynthetically active radiation (PAR), air temperature, vapor pressure deficit (VPD) at one meter in height, besides the surface temperature and temperature of the soil in four depths, through automatic meteorological stations installed in an altitude forest that has two areas with different phytophysiognomies. In a second study, an analysis of the spatial distribution of RFA in the study area was performed to verify the relationship of LAI and basal área (BA) in the transmissivity of the RFA. In the third study, in two seasons of the year, 10 days (5 days in the summer and 5 days in the winter) were selected to verify the regime of sunflecks within the study area. According to the results, the phytophysiognomic differences condition a differentiated microclimate inside the altitude forest, being possible to observe remarkable seasonality and influence of the cloudiness in the microclimatic differences.The area composed of a more closed canopy phytophysiology with a higher index of leaf area attenuates the effects of solar radiation during the day and plays an important role in maintaining energy at night, making the microclimatic variation more stable in comparison with the area that presents a more open canopy phytophysiognomy. In the more open area, higher values of air temperature and maximum VPD were observed, in addition to higher soil temperature. As for the spatial variability of PAR, it was possible to establish an attenuation model in function of the LAI and BA. As for the spatial variability of RFA, it was possible to establish an attenuation model based on LAI and AB. The difference in the phytophysiognomy makes the regime of sunflecks within each area unequal, being in the closed canopy of less intensity and duration compared to the more open phytophysiognomy. The difference in microclimate observed between the two environments probably controls the composition and distribution of the species in the studied forest, thus requiring new studies that investigate the phytosociology and the ecophysiology of the speciesthat compose it.